Sustainability and the culture of the place: the riverine habitat in Amazonia - Virgilio, Marina Fayad; Perdigão, Ana Klaudia de Almeida Viana (National Journal of City Management, 2020)
In this paper, it is investigated the concepts of sustainability by the importance of the culture of the place in the production of architecture. As of a case of study in a riverine housing in the Amazon, it is analyzed the environment built and the speech of the dweller as for healthy life and respect to the place to relate its limits of integration between technical and formal knowledge of sustainability to traditional knowledge in the Amazon habitat. The case of study has an empirical and qualitative character and investigates the present phenomenon into its context of reality with the use of multi-methods. It is highlighted the importance to evidence the theme of sustainability for, in many times, it is not taken into account the proper frames and deepening of cultural and environmental peculiarities. It is aimed to relate the limits of integration between technical and formal knowledge of sustainability with the traditional knowledge in the Amazon habitat based on the analysis of the environment built, crossing it with the speech of users, exploring, this way, some cultural and environmental peculiarities. Thus, the results present formal concepts of architecture in order to understand the profound relation between the environment built and the riverine inhabitant’s way of life. It makes sense to recognize the proper uses still present in the dynamics of life in the Amazon, as a consolidation of citizenship, associated to a search for life quality for, then, thinking about the so called sustainability from the most varied and complex dimensions of the Amazon habitat, which are rather still invisible.